2020
DOI: 10.31545/aagr/126566
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value of de-hulled sunflower seed meal for broilers

Abstract: The effects of de-hulled sunflower seed meal (SFM) samples with different crude protein (CP) and non-starch polysaccharide (NSP) content on apparent metabolizable energy (AME), AME metabolizability (EM) and pre-caecal protein digestibility (pcPD) were examined. The birds were fed one of four mash diets. On a per kilogram basis, the basal diet (BD) contained as major ingredients 549.5 g wheat, 150 g soybean meal and 175 g full fat soybean meal as well as 215.4 g crude protein kg -1 and 12.81 MJ AME kg -1 . Anot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…These results may be because of the increase in CF content from sunflower meal in the diet. Karkelanov et al (2020) found an increase in AME when the SFM (20% of the diet) had low fibre content. Therefore, the de-hulling process is important to reduce the fibre content of DHSS (Senkoylu & Dale, 2006;Viveros et al, 2009).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These results may be because of the increase in CF content from sunflower meal in the diet. Karkelanov et al (2020) found an increase in AME when the SFM (20% of the diet) had low fibre content. Therefore, the de-hulling process is important to reduce the fibre content of DHSS (Senkoylu & Dale, 2006;Viveros et al, 2009).…”
Section: Resultsmentioning
confidence: 87%
“…The fibre content, digestibility, and bioavailability of nutrients in SFM can vary, depending on whether the hulls are included (Laudadio et al, 2014;Karkelanov et al, 2020) and growth performance can alter because of these differences (Khempaka et al, 2009). The main objective of the present study was to evaluate the composition and metabolizable energy of DHSS, and the effects of the partial replacement of SBM with DHSS on the digestibility of nutrients, relative weight of digestive system organs, colour of the breast meat, and performance in finisher broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…It is of broad availability globally, due to its wide adaptability to a range of soil and climatic conditions, it is rich in crude protein content, methionine, and have limited antinutritional factors [7][8][9]. However, its use in broiler feed has been limited by low levels of lysine and high crude fibre, high non-starch polysaccharides concentrations, low metabolizable energy content and some presence of chlorogenic acid [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…SFM is a better choice than SBM because it has more crude protein (280 -420 g/kg), more methionine, and no anti-nutrients (Yusuf et al, 2012). In SFM, the hulls can alter the fiber content, digestibility, and bioavailability of nutrients, and growth performance can be affected as a result (Karkelanov et al, 2020). However, the solubility and concentration levels of fiber in poultry diets can have a significant impact on performance (Tufarelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%